PENGARUH PERBANDINGAN BUBUR ALPUKAT DENGAN SARI MARKISA DAN JUMLAH GUM ARAB TERHADAP MUTU MARGARIN BUAH (The Effect of Avocado Pulp and Passion Fruit Juices Mixtures and Arabic Gum on The Fruit Margarine Quality) - Atika Laila Sari; Herla Rusmarilin; Sentosa Ginting (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT Fruit margarine made from the mixture of avocado pulp and passion fruit juices has a slightly sour in taste, so that salt and sugar were added to improve its organoleptic quality. The aim of this research was to determine the effect of mixture of avocado pulp along with passion fruit juices and arabic gum on the fruit margarine quality. This study used completed randomized factorial design with two factors : the ratio of avocado pulp with passion fruit juice  (80% : 20% ; 65% : 35%; 50% : 50%; 35% : 65%; 20% : 80%) and amount of Arabic gum  (0,75%, 1,00%, 1,25%). The parameters analyzed were moisture  content, ash content, vitamin C content, fat content,  total acid, total soluble solid, color index,  pH, hedonic scales of color, flavor, taste, texture and spreadability. The mixture  of 80% of avocado pulp and 20% passion fruit juice with 1,25% of Arabic gum resulted in the best quality of fruit margarine. Keywords : Arabic Gum, Avocado, Fruit Margarine, Passion Fruit ABSTRAK   Margarine buah dibuat dari campuran daging buah alpukat dan sari buah markisa yang memiliki rasa sedikit asam, sehingga perlu ditambahkan garam dan gula untuk meningkatkan mutu organoleptiknya. Penelitian ini bertujuan untuk menentukan pengaruh campuran daging buah alpukat dan sari markisa serta penambahan gum arab terhadap mutu margarin.  Penelitian dilakukan dengan menggunakan rancangan acak lengkap faktorial dengan dua faktor : perbandingan daging buah alpukat dengan sari markisa (80% : 20% ; 65% : 35%; 50% : 50%; 35% : 65%; 20% : 80%), dan jumlah gum arab (0,75%, 1,00%, dan 1,25%).  Parameter mutu margarin yang diamati adalah kadar air, kadar abu, vitamin C, kadar lemak, total asam, total padatan terlarut, indeks warna, pH, nilai hedonik warna, flavor, rasa, tekstur dan daya oles.  Campuran buah alpukat 80% dan sari markisa 20% dengan penambahan gum arab 1,25% menghasilkan margarin dengan mutu terbaik.   Katakunci : Alpukat, Gum Arab, Margarin Buah, Markisa